2005
DOI: 10.1007/s10162-004-5016-3
|View full text |Cite
|
Sign up to set email alerts
|

On the Coupling Between the Incus and the Stapes in the Cat

Abstract: The connection between the long process and the lenticular process of the incus is extremely fine, so much so that some authors have treated the lenticular process as a separate bone. We review descriptions of the lenticular process that have appeared in the literature, and present some new histological observations. We discuss the dimensions and composition of the lenticular process and of the incudostapedial joint, and present estimates of the material properties for the bone, cartilage, and ligament of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 16 publications
1
59
0
Order By: Relevance
“…The incudomallear joint was not modeled in this study because it has been observed to be rigid at low frequencies (e.g., Guinan and Peake 1967;Gundersen 1976). With respect to the incudostapedial joint, Guinan and Peake (1967) and Decraemer and Khanna (2000) reported relative motion between the incus and stapes, but Funnell et al (2005) concluded that this may be attributable mostly to the pedicle, rather than to the incudostapedial joint-a conclusion that was confirmed by Robles et al (2006) in the chinchilla. The incudostapedial joint was therefore not modeled in this study.…”
Section: Geometry and Materials Propertiesmentioning
confidence: 60%
See 2 more Smart Citations
“…The incudomallear joint was not modeled in this study because it has been observed to be rigid at low frequencies (e.g., Guinan and Peake 1967;Gundersen 1976). With respect to the incudostapedial joint, Guinan and Peake (1967) and Decraemer and Khanna (2000) reported relative motion between the incus and stapes, but Funnell et al (2005) concluded that this may be attributable mostly to the pedicle, rather than to the incudostapedial joint-a conclusion that was confirmed by Robles et al (2006) in the chinchilla. The incudostapedial joint was therefore not modeled in this study.…”
Section: Geometry and Materials Propertiesmentioning
confidence: 60%
“…This decision was based on the work done by Funnell et al (2005), who concluded that the pedicle may not be rigid and may play a major role in the motion between the incus and the stapes. As in their model, a Young_s modulus of 5 GPa was assigned to the pedicle based on the measurements of Mente and Lewis (1994).…”
Section: Geometry and Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the incus and the stapes as viewed along the axis of the microscope objective in the 15 experiments carried out at a 40°a ngle. In chinchilla, as in other species, the long process and the lenticular plate of the incus are connected by a fine bony structure, the pedicle; the incudo-stapedial joint consists of a close apposition of the incus lenticular plate and the stapes head (see (Funnell et al 2005)). Vibrations of both the long process and the lenticular plate of the incus were measured in those 15 chinchillas.…”
Section: Resultsmentioning
confidence: 99%
“…5) suggests that at certain frequencies (15-30 kHz), the vibration of the long process of the incus includes a substantial component along an axis different from that of the piston-like motion of the stapes. In other words, far from boosting vibrations transmitted to the stapes, the incus pedicle appears to insulate the stapes from nonpiston-like motion, as suggested by a finite-element model of the cat middle ear ((Funnell et al 2005); also discussed by (Elkhouri et al 2006)). Threedimensional stapes velocity measurements in gerbil (Decraemer et al 2007a;Ravicz et al 2008) reveal predominantly piston-like stapes motion but also substantial transverse (tilting-like) components at some frequencies.…”
Section: No Boost Of Transmission Across the Incus Pediclementioning
confidence: 89%